Use of anaerobic biodigestor in the treatment of organic waste from a university restaurant. Issue 5 (October 2021) - Granzotto, F.; Aita, C.; Silveira, D.D.; Mayer, F.D.; Pujol, S.B.; Piñas, J.A.V.; Hoffmann, R.
Abstract: Anaerobic digestion (AD) can be a viable treatment option of organic wastes from restaurants, also generating biogas and digestate. Therefore, the aim of this work is to assess the treatment of organic residues from a university restaurant of Federal University of Santa Maria (UFSM). For this purpose, a 200 L semi-pilot scale anaerobic digester was monitored over 240 days, operating at mesophilic temperature in different hydraulic retention times (30 and 60 days). Substrate and digestate pH varied from 4.8 to 6.3 and 6.2–7.3, respectively. The average removal of chemical oxygen demand, biochemical oxygen demand, total solids, sedimentable solids, and volatile solids were 95%, 95%, 53%, 93%, and 77%, respectively. Biogas yield was 0.22 m 3 ∙kg −1 VS or 67 L kg −1 of substrate with 60% of CH4 in average. Despite the variability in substrate composition, the results show high efficiency of the AD operation on decreasing the polluting potential of food waste, simultaneously generating both biogas and digestate, as a potential organic fertilizer. This work is a pioneer in the energy use of food waste from university restaurants in RS-Brazil, providing important information on AD operation, which can be useful in the design of a larger scale plant. Graphical Abstract: ga1 Highlights: Food waste from a university restaurant was treated in an anaerobic digester. a 200 L semi-pilot scale anaerobic digester was monitored over 240 days. Pollution potential was efficiently removed despite the variability in substrate. Biogas yield was 67 L kg −1 of substrate with 60% of CH4 in average. TKN accumulation in biodigester does not reduce methane production.